2011
DOI: 10.1002/pds.2182
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacovigilance for antiretroviral drugs in Africa: lessons from a study in Abidjan, Cote d'Ivoire

Abstract: Background While antiretroviral treatment (ART)-related adverse drug reactions (ADR) are documented in industrialized countries, there is no pre-existing surveillance system dedicated to ADR monitoring in most African countries. We assessed knowledge towards pharmacovigilance among ART prescribers and available capacity of HIV clinics to conduct ADR monitoring in Abidjan, Côte d’Ivoire. Methods A questionnaire was administered to ART prescribers, to assess their knowledge towards the occurrence of ADRs. A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Indeed, in low and middle-income countries long-term safety data of ART is still limited due to the lack of pharmacovigilance systems. Nevertheless, adverse events related to ART are common and represent the first cause of treatment modification in HIV-infected people on ART in sub-Saharan Africa [ 4 , 5 ]. The WHO classifies ART related toxicities into four grades of severity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in low and middle-income countries long-term safety data of ART is still limited due to the lack of pharmacovigilance systems. Nevertheless, adverse events related to ART are common and represent the first cause of treatment modification in HIV-infected people on ART in sub-Saharan Africa [ 4 , 5 ]. The WHO classifies ART related toxicities into four grades of severity.…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed that even though majority of the health-care providers had a positive attitude towards ADR reporting, awareness was low among nursing officers. 21 Our data suggest that health-care providers who had training in pharmacovigilance were better at reporting ADR when compared to those not trained. However, the low awareness amongst nurses poses and important challenge.…”
Section: Discussionmentioning
confidence: 62%
“…Increasing numbers of people living with HIV (PLWH) receive ART—13.5 million people in low- and middle-income countries (LMICs) in 2014 [ 4 ]—driving a clear need to enhance global drug safety monitoring [ 5 , 6 ]. Toxicity from ART is a common reason for patients to switch or stop a medication regimen [ 7 – 10 ]. Adverse drug reactions (ADRs) are characterized by the suspicion of a causal relationship between the drug and the occurrence [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, if a healthcare provider or a patient suspects that a medication may be even partially responsible for a symptom or ADR, then he/she would report it to a national drug safety monitoring center through national channels as part of SR. However, in LMICs, ADRs are often under-reported because of overburdened healthcare systems, significant resource constraints, limited laboratory capacity to identify and manage ADRs, and limited knowledge and unfavorable attitudes among healthcare providers towards reporting [ 9 , 10 , 20 , 23 26 ]. Furthermore, many countries do not have a national system.…”
Section: Introductionmentioning
confidence: 99%